A Rare Life-Threatining Complication of Deep Neck Abscess; Internal Jugular Vein Erosion - Yorgancılar, Ediz; Kınışa, Vefa; Gün, Ramazan; Bakır, Salih; Özbay, Musa; Meriç, Faruk (Fırat University, 2012)
A 16-year-old male was admitted to our hospital with the diagnosis of deep neck abscess due to a dental infection was mentioned. Surgical drainage was applied under local anesthesia. The patient did well for about 2 days. Two days later, acute swelling on patient's neck had began. The computed tomography revealed massive cervical hematoma and right internal jugular vein thrombophlebitis . The neck exploration was made successfully. Vascular complications of deep neck infections are less common but they are still present. We could not find a similar case report of the internal jugular vein erosion and silent hematoma in the neck due to deep neck infection.

On altı yaşında erkek hasta diş enfeksiyonu kaynaklı olduğu düşünülen derin boyun apsesi tanısıyla dış merkezden hastanemize refere edildi. Lokal anestezi altında apseye cerrahi drenaj uygulandı. Hastanın genel durumu 2 gün boyunca iyi seyretti. İki gün sonra, hastanın boynunda akut gelişen bir şişlik başladı. Çekilen bilgisayarlı tomografi, masif servikal hematom ve sağ internal juguler vende tromboflebit olduğunu gösterdi. Cerrahi eksplorasyon başarıyla uygulandı. Derin boyun enfeksiyonlarının damarsal komplikasyonları sık olmamakla birlikte halen görülebilmektedir. Bu hastamıza benzer olarak bildirilmiş, derin boyun enfeksiyonuna bağlı internal juguler ven erozyonu ve sessiz hematom şeklinde bir vaka takdimine rastlamadık.
Derin Boyun Apsesinin Hayatı Tehdit Eden Nadir Bir Komplikasyonu; İnternal Juguler Ven Erozyonu